Pengaruh Literasi Keuangan, Sikap Keuangan, dan Pendapatan Terhadap Perilaku Pengelolaan Keuangan pada UMKM di Waduk Cengklik Boyolali - Novita Eka Putri Hapsari; Setyaningsih SU (Teewan Journal Solutions, 2026)
Cengklik Reservoir in Boyolali Regency plays a dual role as a source of irrigation and a stunning water tourism destination, especially at sunset. However, this place faces the challenge of fluctuating income caused by spikes in tourist visits at certain times. This research was conducted to examine the extent to which financial literacy, financial attitudes, and income influence the financial management behaviour of MSME actors operating around the reservoir. The results of this study are expected to provide an in-depth understanding of the importance of effective financial management for MSME actors. The hypothesis proposed in this study is that there is a significant influence, both individually, of these three variables on the financial management behaviour of MSMEs at Cengklik Reservoir.This study adopts a quantitative approach using a survey method. Data was collected from 154 respondents, consisting of MSME actors at Cengklik Reservoir, through questionnaires. The data used is primary data. The sampling technique was conducted randomly using the cluster random sampling method. Data analysis utilised multiple linear regression, T-test, F-test, and coefficient of determination. Partially, the analysis results showed that financial literacy, financial attitude, and income had a significant effect on financial management behaviour. Based on the coefficient of determination (R2) value of 0.524, it can be concluded that 52.4% of the variation in financial management behaviour is influenced by these three factors. These findings underline the urgency of improving financial literacy, forming positive financial attitudes, and effective income management to achieve MSME financial success